Neurodydaktyczne podłoże klasycznych zasad nauczania – uczenia się dla wykonawstwa solowych instrumentalnych dzieł muzycznych klasycznych - Dymnikowa, Maria; Lasoń, Joanna (Studia Edukacyjne, 2021)
The article combines the classical didactics and neuro-didactics of pedagogical areas, music psychology and instrumental music pedagogy of classical music art areas. The methodological study concerns: – the theme as the process of solo instrumental classical music performance; – the subject as the neuro-didactic basis of classical teaching principles - learning in this process; – the pragmatic scientific novelty as the methodological development of a set of key elements of the lesson as professional workshop activities for this process, for universal use for all musical instruments performed by solo classical music works, for various available forms of professional classical music education; – the practical usage for different levels of classical music education, depending on the level of people’s preparation for solo instrumental classical music performance, and promotion of this activity.